Alkali Metal Complexes: Mixed Ligand Complexes of Some Organic Compounds of Alkali Metals with 4-Isonitroso-1-Phenyl-3-Methyl-5-Pyrazolone. - PRAKASH, D.; KUMAR, B.; GUPTA., O.P. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of alkali metal salts of o-nitrophenol, 2,4-dinitrophenol, 2,4,6-trinitrophenol, 1-nitroso-2-naphthol, 8-hydroxyquinoline, salicylic acid, acetylacetone and o-aminobenzoic acid with 4-isonitroso-, phenyl-3-methyl-5-pyrazolone have been synthesised and characterised on the basis of elemental analysis, conductivity measurement and IR spectral data.